An Analysis of Puccini's opera Turandot from the perspective of modern music philosophy - Hui Han (European Journal for Philosophy of Religion, 2022)
Giacomo Puccini's final play, Turandot (1926), was unfinished when he passed away and is frequently interpreted as an exclusively orientalist production under the guise of his Madame Butterfly. However, I argue that the terrifying search for the human element—which is thought to be missing from the work—provokes a deeper profound reflection on the state of a devastated Italy as a result of the Second Great War. The performativity of orientation and, eventually, of the actual human are frontal sections of Turandot's divided self. The essay analyses the Orientalization of the main characters in Puccini's opera. Turandot serves as an example of how "Orientalizing the Orient" is the process by which Europeans have come to understand Asians. Turandot and Liu, two champions, fit the two extremes of the fabled serpent woman and Butterfly, generalisations of Asian women in the West. Europeans polished and summarised Turandot's ominous and malicious portrayal, as well as Liu's obedient and charitable one, to suit their purposes. Additionally, Cyclone and Calaf independently confront the stereotypes that the public has about China and the West